Prevalence of Patellofemoral Pain Syndrome and Its association with Knee Stiffness in Sanitary Workers: Prevalence of Patellofemoral Pain Syndrome - Hussain, Ghazal; Rasheed, Bibi Fatima; Rashid, Hafiz Hamid; Ashraf, Mariyam; Manzoor, Maham; Naeem, Zainab; Kazmi, Syeda Mishal; Qamar, Siddiqa (Pakistan Journal of Health Sciences, 2023)
Patellofemoral pain syndrome is an overuse injury that causes pain in the front of knee and it’s more common in females. Heavy workload and consistent stress on knee especially in labour work is also affecting male population with this syndrome. It can affect quality of life by limiting functions and it has long term effects. Objective: To determine the prevalence of patellofemoral pain syndrome in sanitary workers who are facing knee stiffness or knee pain. Methods: A sample of 128 participants of age 30-50 years of sanitary workers was included for the survey, according to inclusion criteria. For the selection of participants, convenience sampling was used. Pendulum test, Patellar grind test, and Knee Injury and osteoarthritis outcome score survey for symptoms and pain were used to collect data. An informed consent was signed by the participants stating that personal information of participants is confidential. Results: SPSS version 22 was used to define the descriptive and associated analysis of data. Results showed that there is association between Knee injury and osteoarthritis outcome score symptoms and patellar grind test (p>.0001) while there is no association between knee outcome score pain sign and pendulum test (p=.482). 259 participants reported 71% overall prevalence of patellofemoral pain. Conclusions: It is concluded that male sanitary workers had high prevalence levels of Patellofemoral pain. Preventative measures such as ergonomics training, physical activity should be taken into consideration to enhance quality of life.